Dielectric behavior of CaCu3Ti4O12: Poly Vinyl Chloride ceramic polymer composites at different temperature and frequencies - Ajay Pratap Singh; Y.P. Singh (Modern Electronic Materials, 2016)
In this study, the efforts have been made to obtain relatively high dielectric constant polymer-ceramic composite by incorporating the giant dielectric constant material, calcium copper titanate (CCTO) in a PVC polymer matrix. We have prepared composites of CaCu3Ti4O12 (CCTO) ceramic and Poly Vinyl Chloride (PVC) polymer in various ratios (by volume) in addition to pure CCTO. For this, CCTO was prepared by the conventional oxide route (solid-state reaction method). The structural, the microstructural and the dielectric properties of the composites were studied using X-ray diffraction, Scanning Electron Microscope, and impedance analyzer respectively. The study of dielectric constant and dielectric loss of the pure CCTO and the composites reveal that there is good range of dielectric constants and dielectric losses for the studied composites. The pure sample of CCTO exhibits giant dielectric constant at low frequency within the studied temperature range. As frequency increases, dielectric constant drastically decreases and approaching a constant value at 1 MHz. Above the intermediate temperature, the dielectric constant and dielectric loss for pure CCTO is more frequency dependent than its composites.